Effect of Lactation on myocardial vulnerability to ischemic insult in rats - Askari,Sahar (2017)
Abstract Background: Cardiovascular diseases are the leading cause of mortality and long-term disability worldwide. Various studies have suggested a protective effect of lactation in reducing the risk of cardiovascular diseases. Objective: This study was designed to assess the effects of pregnancy and lactation on the vulnerability of the myocardium to an ischemic insult. Methods: Eighteen female rats were randomly divided into three groups: ischemia-reperfusion (IR), in which the hearts of virgin rats underwent IR (n = 6); lactating, in which the rats nursed their pups for 3 weeks and the maternal hearts were then submitted to IR (n = 6); and non-lactating, in which the pups were separated after birth and the maternal hearts were submitted to IR (n = 6). Outcome measures included heart rate (HR), left ventricular developed pressure (LVDP), rate pressure product (RPP), ratio of the infarct size to the area at risk (IS/AAR %), and ventricular arrhythmias - premature ventricular contraction (PVC) and ventricular tachycardia (VT). Results: The IS/AAR was markedly decreased in the lactating group when compared with the non-lactating group (13.2 ± 2.5 versus 39.7 ± 3.5, p < 0.001) and the IR group (13.2 ± 2.5 versus 34.0 ± 4.7, p < 0.05). The evaluation of IR-induced ventricular arrhythmias indicated that the number of compound PVCs during ischemia, and the number and duration of VTs during ischemia and in the first 5 minutes of reperfusion in the non-lactating group were significantly (p < 0.05) higher than those in the lactating and IR groups. Conclusion: Lactation induced early-onset cardioprotective effects, while rats that were not allowed to nurse their pups were more susceptible to myocardial IR injury.